Profitabilitas Usahatani Padi Anggota Aliansi Petani Padi dan Palawija Organik Boyolali (APPOLI) di Kecamatan Simo - Elhusna, Antariesta Sierra; Setiadi, Agus; Budiraharjo, Kustopo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Organic rice farming has good prospects in terms of increasing land area, production levels and consumer preferences. Profit-oriented farming requires an analysis that is used to measure the ability of the business to generate profits. The study aims to analyze the income and profitability of rice farming of APPOLI members in Simo District. The research location is in three villages in Simo District, namely Wates Village, Temon Village and Sumber Village. The research method used was a survey method with a questionnaire as a research instrument. The sampling technique used a census method of 65 farmers who planted organic rice for three periods in one year. The data used included primary data and secondary data. Data analysis used in the study is the analysis of income and profitability using the R/C ratio. Average income was tested with One Sample Wilcoxon Signed Rank compared to Boyolali Regency minimum wage. Average R/C Ratio tested with One Sample T-Test compared to 1. Data analysis shows that the average rice farms income of APPOLI members in Simo District is 2,551,658 rupiah per month with an average land area of 0.46 ha. The results of the One Sample Wilcoxon Signed Rank test showed that APPOLI members rice farming income in Simo District was not different from the Boyolali Regency minimum wage. The average R/C ratio was 2.08. The One Sample T-Test results show that R/C ratio of APPOLI members rice farms in Simo District are higher than 1, which means it is profitable to run.